Macronutrient, immunoglobulin a and total antioxidant capacity profiles of human milk from 1 to 24 months: a cross-sectional study in Thailand - Krongporn Ongprasert; Jetsada Ruangsuriya; Rungnapa Malasao; Ratana Sapbamrer; Pikul Suppansan; Pisittawoot Ayood; Kulnipa Kittisakmontri; Penprapa Siviroj (BMC, 2020)
Abstract Background An extended duration of breastfeeding of up to two years is encouraged by many health authorities, but information regarding the composition of milk after one year postpartum is limited. The goal of this study was to determine the association between the duration of lactation and macronutrient contents, immunoglobulin A (IgA) levels and total antioxidant capacity (TAC) in human milk (HM), from 1 to 24 months postpartum. Methods Cross-sectional milk samples were collected between January and April 2019 from mothers with healthy full-term children who had been lactating for 1 to 24 months. The HM was biochemically analyzed for protein and carbohydrate contents by colorimetric assays. The fat content was determined by capillary centrifugation, and the energy content was calculated from the results of centrifugation assays. IgA levels and TAC were determined by ELISA and a Trolox equivalent antioxidant capacity (TEAC) assay, respectively. Pearson's correlation coefficient and Spearman's rank correlation coefficient were used to determine associations between months of lactation and milk composition, and multiple regression analysis was used to assess associations between months of lactation and milk composition adjusted for relevant covariates. Differences were considered significant at p < 0.05. Results One hundred eighty-four milk samples were analyzed. The month of lactation was positively associated with the fat concentration (B = 0.31, SE = 0.09, p = 0.001), energy content (B = 3.11, SE = 0.92, p = 0.001), and IgA (B = 4.17, SE = 1.08, p < 0.001) but negatively associated with the carbohydrate concentration (B = − 0.22, SE = 0.01, p = 0.04). No association was observed between the month of lactation and the protein concentration or TAC after adjustment for maternal age, maternal BMI, birth order, and breastfeeding frequency. Conclusion The duration of lactation was found to be positively associated with the fat, energy, and IgA content in HM for up to two years postpartum, and negatively associated with carbohydrate concentration. More prospective cohort studies are needed to obtain evidence-based knowledge regarding the changes in HM composition throughout the course of lactation.